PERAN PENYULUH AGAMA ISLAM DALAM MEMBINA KELUARGA MENUJU KELUARGA SAKINAH DI KELURAHAN TOMPOBALANG KECAMATAN SOMBA OPU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research raises the main problem of "How the Role of Islamic Religious Instructors in Fostering Families Towards Sakinah Families in Tompobalang Village, Somba Opu District, Gowa Regency", with sub-problems, namely: How are the Efforts of Islamic Religious Instructors in Fostering Families Towards Sakinah Families in Tompobalang Village, Somba Opu District Gowa Regency and What are the obstacles of Islamic Religious Instructors in Fostering Families Towards Sakinah Families. The results of this study indicate that the efforts of Islamic religious instructors in fostering families towards sakinah families in Tompobalang Village, Somba Opu District, Gowa Regency, namely: Conducting Routine Counseling, Development of Religious Aspects through Friday 'at worship and the Taklim Assembly. The obstacles experienced by Islamic extension agents in fostering a family towards a sakinah family are: lack of participation from the community, a lack of openness from the community and the community feel that their family is fine.